Brown adipose TRX2 deficiency activates mtDNA-NLRP3 to impair thermogenesis and protect against diet-induced insulin resistance - Huang, Yanrui; Zhou, Jenny H.; Zhang, Haifeng; Canfran-Duque, Alberto; Singh, Abhishek K.; Perry, Rachel J.; Shulman, Gerald I.; Fernandez-Hernando, Carlos; Min, Wang (The Journal of clinical investigation, 2022)
Brown adipose tissue (BAT), a crucial heat-generating organ, regulates whole-body energy metabolism by mediating thermogenesis. BAT inflammation is implicated in the pathogenesis of mitochondrial dysfunction and impaired thermogenesis. However, the link between BAT inflammation and systematic metabolism remains unclear. Herein, we use mice with BAT deficiency of thioredoxin-2 (TRX2), a protein that scavenges mitochondrial reactive oxygen species (ROS), to evaluate the impact of BAT inflammation on metabolism and thermogenesis and its underlying mechanism. Our results show that BAT-specific TRX2 ablation improves systematic metabolic performance via enhancing lipid uptake, which protects mice from diet-induced obesity, hypertriglyceridemia, and insulin resistance. TRX2 deficiency impairs adaptive thermogenesis by suppressing fatty acid oxidation. Mechanistically, loss of TRX2 induces excessive mitochondrial ROS, mitochondrial integrity disruption, and cytosolic release of mitochondrial DNA, which in turn activate aberrant innate immune responses in BAT, including the cGAS/STING and the NLRP3 inflammasome pathways. We identify NLRP3 as a key converging point, as its inhibition reverses both the thermogenesis defect and the metabolic benefits seen under nutrient overload in BAT-specific Trx2-deficient mice. In conclusion, we identify TRX2 as a critical hub integrating oxidative stress, inflammation, and lipid metabolism in BAT, uncovering an adaptive mechanism underlying the link between BAT inflammation and systematic metabolism.